2019
DOI: 10.1155/2019/6430868
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ground Clay Brick Mortars in Simulated Chloride and Sulphate Media

Abstract: The durability of cement-based structures majorly depends on their resistivity to the aggressive media in the construction environment. The most aggressive ions commonly encountered in construction environment are chloride (Cl−) and sulphate (SO42−). The interactions of these ions with hydrated cement influence their durability and ultimate service life. This paper reports the experimental findings on an investigation on the diffusivity of Cl− and SO42− ions into mortars made from two mixtures: one made from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Mechanical mixing had the advantage of saving mixing power and ensuring uniformity. The experiment of some researchers [16][17] showed that the average compressive strength increased with the increase of mixing time.…”
Section: Phase Composition Of Nano-modified Fly Ashmentioning
confidence: 99%
“…Mechanical mixing had the advantage of saving mixing power and ensuring uniformity. The experiment of some researchers [16][17] showed that the average compressive strength increased with the increase of mixing time.…”
Section: Phase Composition Of Nano-modified Fly Ashmentioning
confidence: 99%
“…In addition, due to the high energy demand associated with the production of PC, the resultant cement is expensive, especially to lowincome earners. Blending of PC with pozzolanic materials has been found to be an innovative strategy to lower the cost of cement and reduce the amount clinker and, hence, lower CO 2 emission [18][19][20]. However, blended cements have been found to be susceptible to carbonation than PC due to lower amounts of calcium hydroxide (CH) in their hydrated phases [13,21,22].…”
Section: Introductionmentioning
confidence: 99%